4x^2-9
(2x^3)+(3x^2)+8x+12
Anyone know how to simplify this equation?
Hello,
Note that $\displaystyle 4x^2-9=(2x)^2-3^2$. This is the difference of two squares. (the formula is $\displaystyle a^2-b^2=(a-b)(a+b)$
For the denominator, I'm sorry to say it's just a eyeballing...
$\displaystyle 2x^3+3x^2+8x+12={\color{red}2}x^3+{\color{blue}3}x ^2+{\color{red}2}\cdot 4x+{\color{blue}3} \cdot 4$)
Now, you can see some interesting things. If not yet, group the terms with a common factor.
$\displaystyle =2(x^3+4x)+3(x^2+4)$
Factor x in the first term :
$\displaystyle =2x(x^2+4)+3(x^2+4)$
Do you see it ? The factorisation of the denominator ?